PENILAIAN RISIKO PADA PEKERJAAN BONGKAR MUAT BARANG DI PT. PRIMA ARYA PRATAMA BALIKPAPAN - Maslina, Maslina; Liku, James. E.A; Insani , Getar; Siboro, Impol1 (IDENTIFIKASI, 2023)
Loading and Unloading is one of the activities carried out in the process of forwarding (shipping) goods. What is meant by loading activities is the process of moving goods from the warehouse, raising and then stacking them on the ship, while unloading activities are the process of removing goods from the ship and then arranging them in a warehouse in the port or Stock pile or container yard. In the process of loading and unloading activities, of course, there are many risks and dangers that can occur from every process of loading and unloading work, therefore, a K3 management system is needed to make the work of loading and unloading goods safely done and does not cause potential loss of life, loss, property damage and environmental damage for the company and others. As an effort to prevent work accidents, It is necessary to identify the source of the hazard at work. Without knowing the dangers, accident control and prevention efforts cannot be carried out. Identifying the source of hazards in the work environment will be an essential part of drafting measures to prevent work accidents. One method to identify the source of danger is Hazard Identification and Risk Assessment (HIRA). This research was conducted with qualitative methods. From the results of the study obtained results in the form of 5 stages of work in loading and unloading goods at PT Prima Arya Pratama. There are 10 potential hazards to the work of loading and unloading goods, and control has been carried out using control hierarchy guidelines.